The wife's right to maintenance (nafaqah) in Islam : a juristic appraisal of the law and practice in Brunei Darussalam - Fathiyah Amalina bte DSS Hj Abu Bakar (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Lawsuits initiated by wives for nafaqah, whether current or arrears, abound Shari'ah courts in Brunei. In terms of social implication, it further increases ill-effects associated with divorce and broken marriages as a result of errand husbands abusing their obligation to provide nafaqah to their wives. Accordingly, it is pertinent to address this issue through this research with the aim of educating the public and legal bodies in Brunei. This study focuses on the comparison of nafaqah for the wife under Islamic law and its legislation in Brunei according to the Emergency (Islamic Family Law) Order 1999. This study also discusses the issues of nafaqah in Brunei based on case studies and interviews, and also delineates the current procedures in the Shari'ah Court in Brunei. Statistics on the rise of nafaqah complaints and its arrears application at the Shari'ah Court show that nafaqah issues are common. Lack of understanding on the wife's part about her entitlement to nafaqah is the main reason for ensuring lawsuits pertaining nafaqah. The study therefore concludes that it is pertinent that the wife must be made aware of her right to nafaqah and the husband must not neglect this aspect of obligation towards his wife.